Hubungan Antara Kebiasaan Konsumsi Makanan Kariogenik Dan Menggosok Gigi Pada Anak Serta Pengetahuan Ibu Dengan Kejadian Karies Gigi Di Paud Taman Ceria Surakarta - Prakoso, Harry Maulana, Dwi Astuti SKM. M.Kes, Kusuma Estu Werdani, SKM., M.Kes (2016)
Dental caries on pre-school children frequently occurs due to the habits of cariogenic food consumption, rarely brush their teeth after meal or before off to bed and parents' lack of knowledge about dental caries. This research aims to find the corelation among the habits of cariogenic food consumption, teeth brushing activity and mother's knowledge on dental caries on children at pre-school education (PAUD) Taman Ceria Surakarta. This research is an observational with cross-sectinal approach. Saturated sampling is used and consists of 79 children and 79 mothers. Most of the children consume cariogenik food (64,6%) and rarely brush their teeth (81,0%), while half of the mothers have the knowledge of dental caries (50,6%). Statistic test shows that there is corelation between the habit of cariogenic food consumption and dental caries (p=0,019). However, there isn't corelation between the habit of teeth brushing activity with dental caries (p=0,792) and there isn't corelation between mother's knowledge about dental caries with dental caries occurence (p=0,222).